Spatially Resolved Brillouin Spectral Hole Burning in PMF and SMF - Xiaoxuan Zhong; Hao Liang; Linghao Cheng; Jie Li; Liang Chen; Xiaoyi Bao; Bai-ou Guan (IEEE Photonics Journal, 2018)
We observe the spectral hole burning effect in a polarization maintain fiber (PMF) and a single-mode fiber (SMF) through the interaction between a continuous wave (CW) beam and a high power pulse with two frequency components located around the Stokes and anti-Stokes frequencies of the CW beam. The linewidth of the spectral burning hole is much narrower than that of the intrinsic Brillouin gain spectrum. We experimentally study the position dependent dip formation process in a PMF and an SMF, and explore the possibility of using this narrowed spectral width for distributed temperature and strain sensing with a higher accuracy. A hole burning peak with a linewidth of 9 MHz in a Brillouin gain spectrum with a full-width at half-maximum (FWHM) of 50 MHz is observed in a PMF. Since the frequency measurement accuracy of Brillouin sensor is inversely proportional to the FWHM of detected spectrum, the spectrum hole burning represents a potential for improving the Brillouin peak detection accuracy of distributed Brillouin sensor.